The Rise of a Global God-Image? Spiritual internationalists, the international left and the idea of human progress. - Job, Sebastian (Third World Quarterly, 2009)
For a period that endured so long it came to seem coextensive with Western modernity, durable barriers stood between those who sought political liberation and those who sought spiritual liberation. We are now emerging from that period. The barriers never operated in the same way or to the same extent in all countries, for much the same reason that 'secularism' differed in its effective meaning from country to country. But even in secularism's Anglo-European heartland the division between spirit and politics no longer feels self-evident. This shift cannot help but resonate throughout progressive politics. What we lack are conceptual means for illuminating the shift. The progressive spiritual-political terrain will hardly come into view if it is conceived only in terms of mutual concerns, or shared ethical values, or common campaign work. Pragmatic considerations must be grounded in conceptions of the current world process. Conceptions of the world process must be capable of generating new and fertile responses to many of the deep moral and metaphysical questions which become more insistent in times of rapid—not to say cataclysmic—change. Only in this way can 'progressive social forces', whether belonging to the tradition of the left or to spiritual and religious traditions, help to open up the human vista at a time when 'progress' is pursued nearly everywhere in its narrowest and most lethal forms. This article takes up these issues, emphasising the need for a reorientation of political thought in the face of a world scene stalked by apocalyptic anxieties. The best child of these anxieties may well be an internationally integrative structure which we can refer to as a 'progressive global God-image'.